Assessment of CD4+ cells subpopulations with the expressing CD39 and CD73 ectonucleotidases in children with psoriasis - D. G. Kuptsova; T. V. Radigina; S. V. Petrichuk; N. N. Murashkin; A. A. Khotko; R. A. Ivanov (Медицинская иммунология, 2022)
Purinergic signaling modulates systemic and local inflammatory responses in immune-mediated and autoimmune diseases, including psoriasis. Extracellular ATP is an important factor of purinergic regulation, and its levels are regulated by catalytic effects of CD39 and CD73 ectonucleotidases. The aim of the present study was to estimate the number of regulatory T cells (Tregs), activated T-helper cells (Thact), T-helper type 17 (Th17) expressing CD39 and CD73 ectonucleotidases in children with psoriasis vulgaris, depending on age, disease duration and severity of the pathological process. We have examined a total of 114 children with psoriasis vulgaris (70 girls and 44 boys) and 41 healthy children serving as a comparison group (25 girls and 16 boys). The age of children with psoriasis was 12.5 (10.1-15.8) years, and 12.4 (7.4-16.1) years for the comparison group. The severity of psoriasis was assessed by the PASI and BSA indices. The number of cells with CD39 and CD73 expression on Tregs, Thact and Th17 was estimated by flow cytofluorimetry. The highest number of CD39-expressing cells was found in the Tregs and CD73-expressing cells in Thact, both in children with psoriasis and in the comparison group. The number of CD39+Th17 was lower in children with psoriasis, but CD39+CD73+Thact and CD39+CD73+Th17 were higher than in comparison group (p < 0.05). There was a decreased number of CD73+Tregs, CD39+Thact, CD39+Th17, CD39+CD73+Thact and CD39+CD73+Th17 with age in healthy children (p < 0.05). In patients with psoriasis, the number of CD73+Th17 increased with age. A decrease in CD73+Th17, and an increase in CD39+CD73+ Tregs with higher PASI and BSA indices were detected. An increased PASI (> 10) showed patients with both high and low CD39+Tregs, with CD39+Tregs being reduced in 48% of cases, increased in 35% and normal values in only 17% of cases. Monitoring the numbers of Tregs, Thact and Th17 cells expressing CD39 and CD73 in children with psoriasis may be used to evaluate chronic inflammation, given the role of CD39 and CD73 ectonucleotidases in shaping the immune response in immune-mediated diseases,